Electro-oxidation of ascorbic acid on perovskite-modified electrodes - Sebarchievici Iuliana; Tăranu Bogdan; Rus Florina Stefania; Vlazan Paulina; Poienar Maria; Sfirloaga Paula; International Symposium on Analytical and Environmental Problems (25.) (2019) (Szeged) (2019)
The main purpose of this research was to obtain LaMnO3 perovskite-modified graphite electrodes, to characterise them and to observe their electrochemical behaviour in the presence of ascorbic acid. The morphology of the perovskite films were studied by scanning electron microscopy (SEM) and their double-layer capacitance was determined using cyclic voltammetry. The results are promising, but the electrocatalytic activity of the films for the oxidation of ascorbic acid needs to be improved.